Comparison of body fat percentages, speed, strength and power among male boxers based on winner and non winner / Mohd Hanifa Sariman - Sariman, Mohd Hanifa (2012)
Background and Purpose. Boxing is a combat sport where the boxers collect point by punching to a target area. Boxing is an individual sport where courage, speed, strength, power, accuracy and passion are utterly important .The purpose of this study was to identify the profiling and comparing the body fat percentage, speed, strength and power of male boxers between the winner and non-winner. Methods. An ex post facto design was employed. Thirty five male boxers [ n= 35; mean height 168.00 (±6.03) cm, weight 59.49kg (±10.12); and BMI 21.01 (±2.93) based on winner and non winner who selected during the National Youth Boxing Tournament. Several tests were conducted in the following sequence: (i) weight and height measurement was taken; (ii) skinfold test using skinfold caliper; (iii) hand grip test to test the hand strength using hand grip dynamometer; (iv) power test using Vertec device - vertical jump test to measure the power of the boxers; (v) 30 m sprint test to measure the speed of the boxers. Results. Body fat percentages reported no significance difference (p >.05) among winner and non winner boxers. Speed showed significantly difference (p < 0.05) among winner and non winner boxers. Strength showed significantly different (p < .05) between winner and non winner boxers. Power showed significantly different (p < .05) between winner and non winner. Discussion and Conclusion. It was concluded that body fat percentage did not show significant difference between winner and non winner boxers. Boxing sport had a define influence of speed, strength and power between winner and non winner where winners exhibited superiority over non winner. Besides that, excellent boxers were good in fitness component. It was recommended that boxing should include other measurement such as physiological profile.